Myrtucomvalones A–C, three unusual triketone–sesquiterpene adducts from the leaves of Myrtus communis 'Variegata'. Issue 37 (25th April 2017) - Chen, Ming; Chen, Li-Feng; Li, Man-Mei; Li, Ni-Ping; Cao, Jia-Qing; Wang, Ying; Li, Yao-Lan; Wang, Lei; Ye, Wen-Cai
Abstract : The first examples of triketone–cubebane adducts (1 and2 ) with an unusual skeleton were isolated from Myrtus communis 'Variegata'. Abstract : Three new triketone–sesquiterpene adducts, myrtucomvalones A–C (1–3 ), along with four known compounds (4–7 ) were isolated from the leaves of Myrtus communis 'Variegata'. Compounds1 and2 are the first examples of triketone–cubebane hybrids with an unusual carbon skeleton. Their structures with absolute configurations were determined by spectroscopic data, single crystal X-ray diffraction and electronic circular dichroism (ECD) analyses. Compounds1–7 displayed inhibitory activities against respiratory syncytial virus (RSV).